Gene therapy for Leber congenital amaurosis advances and future directions - Hufnagel, Robert B. (Graefes Arch Clin Exp Ophthalmol, 2012)
BACKGROUND: Leber congenital amaurosis (LCA) is a congenital retinal dystrophy that results in significant and often severe vision loss at an early age. Comprehensive analysis of the genetic mutations and phenotypic correlations in LCA patients has allowed for significant improvements in understanding molecular pathways of photoreceptor degeneration and dysfunction. The purpose of this article is to review the literature on the subject of retinal gene therapy for LCA, including historical descriptions, preclinical animal studies, and human clinical trials. METHODS: A literature search of peer-reviewed and indexed publications from 1996–2011 using the PubMed search engine was performed. Key terms included “Leber congenital amaurosis”, LCA, RPE65, ”cone-rod dystrophy”, “gene therapy”, and “human trials” in various combinations. Seminal articles prior to 1996 were selected from primary sources and reviews from the initial search. Articles were chosen based on pertinence to clinical, genetic, and therapeutic topics reviewed in this manuscript. Fundus photographs from LCA patients were obtained retrospectively from the clinical practice of one of the authors (R.A.S). RESULTS: Herein, we reviewed the literature on LCA as a genetic disease, the results of human gene therapy trials to date, and possible future directions towards treating inherited retinal diseases at the genetic level. Original descriptions of LCA by Theodor Leber and subsequent research demonstrate the severity of this disease with early-onset blindness. Discoveries of the causative heritable mutations revealed genes and protein products involved in photoreceptor development and visual transduction. Animal models have provided a means to test novel therapeutic strategies, namely gene therapy. Stemming from these experiments, three independent clinical trials tested the safety of subretinal delivery of viral gene therapy to patients with mutations in the RPE65 gene. More recently, efficacy studies have been conducted with encouraging results. CONCLUSIONS: Initial safety studies indicated promising results of subretinal delivery of viral vector with subclinical immunologic or surgical sequelae. Overall, these initial studies demonstrate that viral vector gene therapy results are very promising, safe, and effective. Future studies measuring potential improvement in photoreceptor function may rely on recent advances in retinal imaging and electrophysiologic testing.